Interaction of Chlorpyrifos with Purine Bases: A Study of Electrochemical Measurement and Density Functional Theory Calculation - Song, L.Z.; Zhou, W.Y.; Wang, X.L.; He, J.; Han, K.D.; Niu, L.J. (Asian Journal of Chemistry, 2015)
Interactions of chlorpyrifos with the purine bases involving guanine, adenine and xanthine were investigated, using cyclic voltammetry, anodic differential pulse voltammetry, electrochemical impedance spectroscopy and density functional theory calculations. Bonding constants of the chlorpyrifos-purine base complexes were calculated. The global density functional theory descriptors including chemical potential, electronegativity and electrophilicity index were employed to evaluate the chemical reactivity of chlorpyrifos and purine bases. The condensed Fukui function was calculated to reveal the reactive sites of chlorpyrifos and purine bases. The interaction energies between chlorpyrifos and the purine bases were also calculated. Chlorpyrifos interacts as an electrophile with guanine, adenine and xanthine, showing a certifiable toxicity to the purine bases. The interactions of chlorpyrifos with the purine bases follow the order of guanine > adenine > xanthine. Compared with other two chlorpyrifos-purine base complexes, the chlorpyrifos-guanine complex exhibits larger bonding constant, higher charge transfer and more negative interaction energy.